International Academy of Manual / Musculoskeletal Medicine Bratislava, October 2012. (1st April 2013) - Patijn, Jacob; Beyer, Lothar; Patijn, Jacob; Beyer, Lothar; Biedermann, Heiner; Patijn, Jacob; Foell, Jens; Beyer, Lothar; Puta, Christian; Weiss, Thomas; Hornáček, Karol; Kuzdzal, Adrian; et al.
<x xml:space="preserve">Abstract</x> Introduction The first year of life offers a unique insight into the interaction of function and form. Functional pathology - the core issue of manual medicine - has a far bigger influence on development than later in life. Materials and methods Based on 20 years of practical experience and more than 30 000 babies treated, the effect of spinal manipulation is demonstrated by analysing a random sample of 150 babies treated for 'excessive crying' (drawn from the 1277 babies treated in 2006). Results In more than half of these cases a complete normalization could be achieved by one treatment in the ensuing week. Other than one antero-posterior X-ray of the cervical spine, no investigative diagnostics were necessary. All of these children - and their families - suffered from weeks of crying; other therapies were completely unsuccessful, which led them to seek help in our consultation. Discussion The effectiveness of manual therapy in these cases seems to be obvious enough to warrant serious consideration in the treatment of soi-disant colic. For systematic studies, we shall need the co-operation of paediatric clinics.